Pengaruh Struktur Aset, Risiko Bisnis, dan Pertumbuhan Penjualan Terhadap Struktur Modal Dengan Profitabilitas Sebagai Variabel Moderating - Usi Meilani; Agus Wahyudin (Universitas Katolik Soegijapranata Semarang, 2021)
This study aims to analyze and describe the effect of asset structure, business risk and sales growth on capital structure by using profitability as a moderating variable in property and real estate companies listed on the Indonesia Stock Exchange in 2017-2019. The sample of this research is 49 companies with 147 units of analysis. The sampling method used is purposive sampling. The data collection technique in this study uses the documentation technique in the form of company financial statement data. Data were analyzed using descriptive statistical analysis techniques and inferential statistical analysis with Moderated Regression Analysis (MRA). Data analysis was performed using IBM SPSS Statistics 23. The results of this study indicate that asset structure has a positive and significant effect on capital structure. Business risk and sales growth have no effect on the capital structure. Profitability is able to moderate the effect of asset structure and business risk on capital structure but is unable to moderate the effect of sales growth on capital structure. Business risk and sales growth have no effect on the capital structure. Profitability is able to moderate the effect of asset structure and business risk on capital structure but is unable to moderate the effect of sales growth on capital structure. Business risk and sales growth have no effect on the capital structure. Profitability is able to moderate the effect of asset structure and business risk on capital structure but is unable to moderate the effect of sales growth on capital structure.